Sosialisasi Dampak Sampah Laut sebagai Upaya Peningkatan Kepedulian Masyarakat Terhadap Lingkungan di Desa Pesisir Besuki, Kabupaten Situbondo - Wazirotus Sakinah; Saifurridzal; Dina Tri Septiningtyas; Pratama Yuli Arianto (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2022)
Plastic waste is generally discarded in waters from the river that will eventually empty into the sea and directly discharged into the high seas as happened in the village of Pesisir Besuki, Situbondo district. The problems faced by partners are the lack of public awareness of the short-term and long-term impact of waste disposal activities in the waters and poor management of waste management. So that required waste socialization that include the guidance in environmentally friendly waste management and able to increase awareness of coastal communities to care for the environment. This community dedication use socialization as method with questionnaire before and after activity. The results obtained after the activities carried out are increasing the insight of the people of the Pesisir Village, Besuki District and increasing awareness of the environment so that they are trying to manage the waste they produce independently. According to the questionnaires result, before socialization waste management in Besuki Coastal Region has percentage 73% citizen throw their wastes in the sea or/and the river, 27% has been burned, and 0% in temporary garbage disposal. After socialization, it became 13% throw their waste in the sea or/and the rever, 7% in temporary garbage disposal, and 80% choose to burn their wastes. Generally, they does not have the basic knowledge about marine debris impact with percentage up to 80% and the citizen who know about the knowledge is 20%. Their interest about self waste management is 33%. But after socialization, it became 67% for their interest. Keywords : Waste socialization, Waste Management, Environmental Care